An Examination of Arab States Integration between 1967-1973 - فخر الدين جلال (Dirasat in Economics and Business, 1976)
The aim of this paper is to examine the degree of integration among the Arab states by testing the propostion that beginning with the 1 967 Arab-Israeli war, there can be traced a tendency toward a more cohesive relationship among the Arab states, and this is reflected in their position during the October 1973 war with Israel.